2015
DOI: 10.3389/fncel.2015.00433
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen administration modulates hippocampal GABAergic subpopulations in the hippocampus of trimethyltin-treated rats

Abstract: Given the well-documented involvement of estrogens in the modulation of hippocampal functions in both physiological and pathological conditions, the present study investigates the effects of 17-beta estradiol (E2) administration in the rat model of hippocampal neurodegeneration induced by trimethyltin (TMT) administration (8 mg/kg), characterized by loss of pyramidal neurons in CA1, CA3/hilus hippocampal subfields, associated with astroglial and microglial activation, seizures and cognitive impairment. After T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 155 publications
(227 reference statements)
6
41
3
Order By: Relevance
“…or vehicle (sesame oil). The dose of E2 was chosen in accordance with beneficial effects described in our previous study in TMT-treated adult rats ( Corvino et al, 2015 ) and with previously reported early treatment with E2 associated with neuroprotective effects in neonatal rats ( Pansiot et al, 2016 ). The same E2/vehicle dose was administered on post-treatment day 1 (P6).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…or vehicle (sesame oil). The dose of E2 was chosen in accordance with beneficial effects described in our previous study in TMT-treated adult rats ( Corvino et al, 2015 ) and with previously reported early treatment with E2 associated with neuroprotective effects in neonatal rats ( Pansiot et al, 2016 ). The same E2/vehicle dose was administered on post-treatment day 1 (P6).…”
Section: Methodsmentioning
confidence: 99%
“…E2 is not only able to counteract neuronal death, but also exerts neuroprotection by enhancing neural plasticity, particularly at the hippocampal level ( Brinton, 2009 ). Numerous studies provide evidence that E2 exerts neuroprotective effects by inducing phenotypic changes in the size of different GABAergic subpopulations, in particular enhancing neuropeptide Y (NPY) expression ( Nakamura and McEwen, 2005 ; Corvino et al, 2015 ) and modulating the size of PV-positive interneuron subpopulation ( Rewal et al, 2005 ; Macrì et al, 2010 ). Because of the relevance of hippocampal dysfunction and interneuron imbalance in neurodevelopmental and neuropsychiatric diseases, in the present study we investigated the effects of pretreatment with E2 on different aspects related to TMT-induced hippocampal injury in neonatal rats, including neuronal death, neuroinflammation and interneuron impairment, with the aim of providing an exhaustive description of cellular and molecular events related to possible neuroprotective approaches in early hippocampal damage.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in GAD results in a suppression of the conversion of glutamate to GABA and therefore effectively down regulates GABA. 30 We acknowledge this mechanism of GABA regulation has not been confirmed in the spinal cord, but maintain its plausibility as it is present in both the hippocampus 26 and striatum. 17 Furthermore, it is well established that in patients with conditions such as spinal cord injury and other spasticity related conditions, PI is diminished and represents a decrease in control and modulatory capability of the system.…”
Section: F I G U R Ementioning
confidence: 97%
“…The role of estradiol in the regulation of reactive synaptogenesis under neurodegenerative conditions has also been analyzed in other neuropathological models. In a model of hippocampal neurodegeneration in ovariectomized female rats, induced by the intraperitoneal administration of the neurotoxic trimethylin, the neuroprotective actions of estradiol were associated with the upregulation of the expression of genes involved in synaptogenesis, such as Bcl2, trkB, cadherin 2 and cyclin-dependent-kinase-5 (Corvino et al, 2015; Table 2). However, synaptogenesis was not directly assessed in this study and the upregulated genes also participate in other cellular functions, including the regulation of apoptosis.…”
Section: Neuritogenesis Synaptogenesis and Neuronal Plasticitymentioning
confidence: 99%
“…In the kainic acid rat model of excitotoxic injury, the hormone promotes the survival of somatostatin and neuropetide Y immunoreactive hilar interneurons in ovariectomized rats (Azcoitia et al, 1998;Velísková, 2006;Table 2). In another hippocampal model of neurodegeneration, the administration of trimethylin to ovariectomized rats, estradiol increases the expression of the interneuronal markers glutamic acid decarboxylase 67, neuropeptide Y and parvalbumin (Corvino et al, 2015;Table 2). Estradiol also prevents the reduction in parvalbumin expression in ovariectomized rats submitted to MCAO ischemic brain injury and in hippocampal neuronal cultures exposed to glutamate (Koh, 2014).…”
Section: Excitatory and Inhibitory Neuronsmentioning
confidence: 99%